2015
DOI: 10.4238/2015.september.22.9
|View full text |Cite
|
Sign up to set email alerts
|

Cloning, molecular characterization, and expression pattern of FGF5 in Cashmere goat (Capra hircus)

Abstract: ABSTRACT. Fibroblast growth factor 5 (FGF5) is a secreted signaling protein that belongs to the FGF family, and was found to be associated with hair growth in humans and other animals. The Inner Mongolia Cashmere goat (Capra hircus) is a goat breed that provides superior cashmere; this breed was formed by spontaneous mutation in China. Here, we report the cloning, molecular characterization, and expression pattern of the Cashmere goat FGF5. The cloned FGF5 cDNA was 813 base pairs (KM596772), including an open … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 17 publications
1
3
0
Order By: Relevance
“…In the reproductive system studies, FGF5 showed specific expression in Sertoli cells in mouse testes [36]. Another study demonstrated that FGF5 was expressed extremely higher in the testis compared with those in the liver and pancreas in Cashmere goat, indicating it may be involved in the regulation of spermatogenesis [25]. In our study, FGF5 was verified to be significantly expressed higher in Sertoli cells from males with normal spermatogensis, compared with SCOS patients.…”
Section: Discussionsupporting
confidence: 67%
See 1 more Smart Citation
“…In the reproductive system studies, FGF5 showed specific expression in Sertoli cells in mouse testes [36]. Another study demonstrated that FGF5 was expressed extremely higher in the testis compared with those in the liver and pancreas in Cashmere goat, indicating it may be involved in the regulation of spermatogenesis [25]. In our study, FGF5 was verified to be significantly expressed higher in Sertoli cells from males with normal spermatogensis, compared with SCOS patients.…”
Section: Discussionsupporting
confidence: 67%
“…It has been reported that FGF5 acts as a mitogen to stimulate the proliferation of mesenchymal fibroblasts and mesenchymal stem cells [23]. As for the reproductive system, it has been demonstrated that FGF5 was mainly expressed in mouse Sertoli cells and also displayed plenty of expressions in goat testes [24, 25]. However, the function of FGF5 in male reproduction regulation remains unclear.…”
Section: Introductionmentioning
confidence: 99%
“…; Bao et al . ). As a regulator of hair length, FGF5 has been previously reported in a variety of mammals.…”
Section: Resultsmentioning
confidence: 97%
“…Interestingly, all of the proposed or candidate genes responsible for hair length are attributed to fibroblast growth factor 5 (FGF5). So far, a number of spontaneous mutations of FGF5 associated with hair length have been identified in humans , mice , dogs , cats , donkeys , goats and hamsters . It is indicative that the FGF5 gene is the leading candidate for hair length variation.…”
Section: Introductionmentioning
confidence: 99%